1983
DOI: 10.1021/bi00292a014
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of porcine pancreatic phospholipase A2 and its zymogen induced by submicellar concentration of negatively charged detergents

Abstract: The interaction of two sodium n-alkyl sulfates (C10 and C12) with porcine pancreatic phospholipase A2 and its zymogen was studied by various spectroscopic techniques, equilibrium gel filtration, calorimetry, and photochemically induced dynamic nuclear polarization 1H NMR. At very low concentrations of n-alkyl sulfate [up to 0.07 X critical micelle concentration (cmc)] the enzyme (Mr 14 000) is able to build up a complex with the detergent molecules having a molecular weight of about 90 000. This complex consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 28 publications
5
28
1
Order By: Relevance
“…This suggested that the mole ratio of the anionic amphiphile to the enzyme, rather than its absolute concentration, was responsible for the protection of PLA2 against alkylation. Furthermore, maximum protection at LIE <50 is consistent with previous studies using a variety of techniques which showed that 30-60 molecules of amphiphiles are required for the binding of PLA2 to the interface (Hille et al, 1983;Jain et al, 1982;Jain & Berg, 1989;Yuan et al, 1990). Thus maximum protection required that the LIE ratio exceed 50 regardless of the critical micelle concentration of the amphiphile.…”
Section: Principles and Experimental Strategy For Determiningsupporting
confidence: 89%
“…This suggested that the mole ratio of the anionic amphiphile to the enzyme, rather than its absolute concentration, was responsible for the protection of PLA2 against alkylation. Furthermore, maximum protection at LIE <50 is consistent with previous studies using a variety of techniques which showed that 30-60 molecules of amphiphiles are required for the binding of PLA2 to the interface (Hille et al, 1983;Jain et al, 1982;Jain & Berg, 1989;Yuan et al, 1990). Thus maximum protection required that the LIE ratio exceed 50 regardless of the critical micelle concentration of the amphiphile.…”
Section: Principles and Experimental Strategy For Determiningsupporting
confidence: 89%
“…Formation of enzyme aggregates has been concluded to be involved in the activation of PLA2 [100,101] and we showed the burst in activity to be accompanied by an enhanced Thioflavin T fluorescence, followed by the formation of Congo red staining more macroscopic fibrils [98]. Using fluorescently labelled PLA2 we demonstrated FRET between the enzyme to peak at burst and the incorporation of the fluorescent PLA2 into the fibrils.…”
Section: Amyloid Formation As An On-off Switch For Enzyme Activitymentioning
confidence: 60%
“…As membranes comprising a single phospholipid molecular species do not exist and detergent is absent under most physiological conditions, a result obtained using artifi cial phospholipid membranes may not refl ect the true enzymatic properties of a given sPLA 2 . An exception is sPLA 2 -IB, for which a detergent (bile acid) is important for full enzymatic activity in the intestinal lumen ( 27 ). Ideally, the enzymatic activity of each sPLA 2 isoform should be evaluated at a physiologically relevant enzyme concentration and with a physiologically relevant membrane on which the enzyme acts intrinsically.…”
Section: S Participate In Diverse Biologicalmentioning
confidence: 99%